Pengaruh Profitabilitas, Likuiditas, Pertumbuhan Penjualan, Struktur Modal Dan Free Cash Flow Terhadap Kebijakan Dividen (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2015 – 2017) - Nurul Ruliyanti; Angela Dirman (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
This study aims to determine the effect of profitability, liquidity, sales growth, capital structure and free cash flow on dividend policies as measured by the dividend payout ratio (DPR). Profitability in this study is measured using the ratio of return on assets (ROA), liquidity is measured by the ratio of the current ratio (CR), sales growth is measured by sales growth, capital structure is measured by the ratio of debt to equity (DER) and free cash flow is measured by free cash flow (FCF). The population used is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015 - 2017. The samples used in this study were 34 companies that were selected using the purposive sampling method. This research was conducted using a quantitative descriptive approach. Analysis of the data used in this study is a multiple linear regression model. Partial research results (t test) show that profitability has a positive effect on dividend policy and capital structure has a negative effect on dividend policy, while liquidity, sales growth and free cash flow have no effect on dividend policy. While the results of the simultaneous study (F test) show that profitability, liquidity, sales growth, capital structure and free cash flow affect dividend policy.